(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Increasingly knowledgeable consumers, with rising demands to have information available for them to make appropriate health care decisions, have driven healthcare managers and administrators to focus on an improvement of the service quality to increase patient’s satisfaction. As efforts, many of them are trying to adapt well-established, successful business models like total quality management (TQM), and quality function deployment (QFD) and also trying to learn in what aspects of the health care service provision generate or inhibit patient satisfaction. The primary objective was to discuss issues when employing the models to health care industries.